Pemanfaatan Ekstrak Biji Cerakin (Croton tiglium L) Sebagai Insektisida Nabati Terhadap Ulat Daun Bawang (Spodoptera exigua Hubn) - Ratman, Ratman; Said, Irwan; Jannah, Nif’atul (Jurnal Akademika Kimia, 2016)
The research aim is to determine the ability of cerakin seeds as natural insecticide on caterpillar leek (spodoptera exigua Hubn). In this study, the cerakin seeds from Saloya village, Labuan Panimba village Donggala, and Sidole Village Ampibabo, Central Sulawesi are used as sample. The cerakin seeds was extracted by using ethanol and then were tested on caterpillar leek (spodoptera exigua) with a concentration of extract 15, 25, 35, 45 and 55%. The results showed that for each concentration showed vary results in killing larvae of caterpillar leek (spodoptera exigua), the higher concentration the more mortality of caterpillar leek’s larvae (spodoptera exigua). Therefore it can be stated that the extract of cerakin seeds can be used as an natural insecticide on caterpillar leek (spodoptera exigua) and is also able to kill the larvae caterpillar leek (spodoptera exigua) 93.3% to 100%.